403 Anger contributes to mood disturbances in lupus patients. (14th December 2022) - Sherrod, Sydney; Anderson, Erik; Aranow, Cynthia; Mackay, Meggan
Abstract : BACKGROUND: SLE is typically characterized by organ-specific involvement driven by inflammatory mechanisms, however, patients also exhibit more diffuse syndromes, including depression, anxiety, cognitive dysfunction, fatigue, generalized pain, and sleep disturbances, that significantly impact quality of life, yet are infrequently assessed and not easily attributed to inflammatory mechanisms. Our previous neuroimaging studies combined with neuropsychological (NP) testing have demonstrated that lupus brains can be structurally and functionally different than healthy control (HC) brains and regional metabolic and microstructural abnormalities correlated with poor performance on memory testing and increased depression, anxiety and fatigue irrespective of potentially confounding variables (medication use, disease duration, disease activity).(1, 2) These reports suggest an insidious, SLE-related inflammatory process in the brain resulting in altered cognitive abilities and emotional responses. We have also reported that self-reported anger in SLE correlates significantly with increased orbitofrontal cortex (OFC) metabolism.(2) The OFC has a role in modulating emotional behavior with connections to multiple brain regions including the amygdala, hippocampus, hypothalamus and caudate. These data suggest that anger may be another mood disorder that is increased in SLE and related to SLE-associated mechanisms. OBJECTIVES: Primary Objective: To determine whether SLE patients have a greater frequency of anger compared to HC. Secondary Objectives: To determine relationships in SLE patients between anger and 1. other mood disorders and cognitive function, 2. demographic variables 3. SLE-specific variables METHODS: Participants: Data from adult subjects ≥ age 18 from 2 prior studies were used for this retrospective study of 116 SLE and 74 HC.(3 2) Key exclusion criteria included poor fluency in English, past history of a CNS event or NP disorder, history of substance abuse or current narcotic or psychiatric medication use. SLE subjects met ACR or SLICC criteria and HC had no medical or psychiatric conditions and were on no medications other than oral contraception. Assessments: The Automated Neuropsychological Assessment Metrics (ANAM) was used to assess self- reported mood and cognition. ANAM Mood assessments included anger, depression, anxiety, fatigue and happiness. Subjects were presented with 6 adjectives related to each mood dimension and asked to rate agreement with each adjective on a 7 point scale (0, no agreement, - 6, high agreement). Mood scores are represented as mean values for all 6 adjectives or as a percentage score reflecting mood intensity. Depression was also assessed with the Beck Depression Index (BDI). Cognitive tests included Simple Reaction Time (SRT), Running Memory Continuous Performance Test (CPT), Match to Sample (MTS), and Matching Grids (MG). Throughput scores, representing efficiency (accuracy as a function of response time) were used for MG, MTS, CPT; mean reaction times were used for SRT. Disease activity and damage were assessed with the SELENA-SLEDAI and SLICC Damage Index, respectively. Socioeconomic status was assessed using subject zip code to obtain median household income (United States Census Bureau). Analyses: A Mann-Whitney U test was used to analyze differences in demographics, ANAM cognitive tests, mood scores between SLE and HC, and SLE with/without anger. Chi square tests or Fisher's exact tests were used to analyze differences in categorical variables. Spearman's Correlations were performed among anger scores and BDI, other mood scores, cognitive test scores, and SLE-associated variables. For all, p values <0.05 were considered significant. RESULTS: SLE vs. HC No differences in age, sex, ethnicity/race between SLE and HC. SLE had fewer years of education and lower median household income than HC. (table 1) Compared to HC, SLE demonstrate significantly higher frequencies of anger scores > 0 (SLE 44%, HC 12%, p <0.001) (range of mean anger scores is shown in figure 1) higher frequencies of depression, anxiety, fatigue (table 2) lower frequencies of happiness (table 2) higher mean reaction times and lower throughput scores on the 3 cognitive tests (table 2) Among SLE, the mean intensity of anger scores was 13.9% compared to higher intensities in self-reported depression (16.7%), anxiety (16.7%) and fatigue (47.2%). SLE demonstrated a range of disease activity, damage, active serology and medication use SLE with Anger (SLE-A+) vs. without Anger (SLE-A-) No significant differences between SLE-A+ (n=51) and SLE-A- (n=65) in age, sex, ethnicity/race, education, median household income, disease duration, activity or damage, serology, medication use or co-morbid disease. SLE-A+ demonstrate significantly higher levels of self-reported depression (SLE-A+ 70%, SLE-A- 26%, p <0.001), anxiety (SLE-A+ 92%, SLE-A- 54%, p <0.001) fatigue (SLE-A+ 61%, SLE-A- 19%, p <0.001) lower happiness scores (SLE-A+ 43%, SLE-A- 68%, p<0.008) and CPT throughput scores (SLE-A+ 66.6±22.4, SLE-A- 77.2±15.4, p =0.013). Correlations between Anger, other Mood Scores and Cognitive Testing in SLE Mean anger scores among SLE subjects correlated positively with BDI depression scores (r=0.321, p <0.001), ANAM depression (r=0.683, p <0.001), anxiety (r=0.630, p<0.001), and fatigue scores (r=0.447, p <0.001) negatively with ANAM happiness (r=-0.276, p =0.003) and CPT scores (r=- 0.301, p =0.001) No correlations found with disease duration, activity, damage, serology, medication use CONCLUSIONS: SLE patients have a higher frequency of anger than HC. High anger scores do not associate with demographic or disease-specific variables, including disease activity and corticosteroid dose, do associate with other mood disturbances (depression and anxiety) and fatigue that are frequently reported in SLE. Anger also correlated with poor performance on the CPT test of working memory, retention and vigilance. Our findings suggest that anger is an important mood disturbance in SLE that has been previously unrecognized. Future plans include a prospective study to investigate anger frequency and relationships with brain imaging abnormalities, quality of life and adherence with follow-up visits and medication use. References: Mackay M, Tang CC, Volpe BT, Aranow C, Mattis PJ, Korff RA, et al . Brain metabolism and autoantibody titres predict functional impairment in systemic lupus erythematosus. Lupus Sci Med . 2015;2 (1):e000074. Mackay M, Vo A, Tang CC, Small M, Anderson EW, Ploran EJ, et al . Metabolic and microstructural alterations in the SLE brain correlate with cognitive impairment. JCI Insight . 2019;4 (1). Anderson EW, Fishbein J, Hong J, Roeser J, Furie RA, Aranow C, et al . Quinolinic acid, a kynurenine/tryptophan pathway metabolite, associates with impaired cognitive test performance in systemic lupus erythematosus. Lupus Sci Med . 2021;8 (1).